Enhanced Hardness and Corrosion Resistance of Zn/SiO2 Films by Electrodeposition. Issue 9 (30th June 2015) - Ghorbani, M.; Salehi, F.; Razavizadeh, O.
Abstract : The electrodeposition of Zn-SiO2 nanocomposites has been investigated with different electrolytes: triethanolamine as a dispersing agent, and cetyl trimethylammonium bromide and dodecyl dimethylamine oxide as ionic (cationic) and non-ionic surfactants. Appropriate electrophoretic potentials for each solution were obtained using cyclic voltammetry. The results show that the most stable SiO2 nanoparticles with zeta potential range of 25 to 41 mV, alongwith highest SiO2 mobility of 0.4 to 0.7 m 2 /V.s were dispersed by triethanolamine in ethanol and the resulting coating adhesion improved up to 5.87 MPa in the standard pull off test, with the enhanced hardness of up to 800 HV. The coating thickness has been seen to increase with increasing potential. The coating morphology investigations reveal three different morphologies for different electrolytes: instantaneous coaxial grain growth for water, hexagonal grain growth for methanol and amorphous structure for ethanol. Corrosion properties of the zinc nanocomposite coatings are discussed where samples with low SiO2 (<10 wt.%) concentrations are shown to possess higher corrosion resistance than high SiO2 (>10 wt.%) concentrations.